Actualité de la pensée de Georges Millardet en linguistique et dialectologie romanes à travers sa contribution à la RLaR - Jean Léo Léonard (Revue des Langues Romanes)
With his two “king size papers” published in 1921–3 in the Revue des Langues romanes (RLaR) —actually a preprint of a major essay in Romance linguistics and dialectology—, Georges Millardet deserves to be considered as one of the precursors of the paradigm of General Dialectology (when dialectology meets theoretical and formal linguistics). The prepublication of this seminal essay constitutes a milestone in the history of Romance studies, especially for the epistemological development of Romance linguistics. The author, siding with Maurice Grammont's skepticism vis-à-vis the linguistic geography of the Paris school, dominated by Jules Gilliéron, rehabilitates the Neogrammarian comparative method, opening up pioneering prospects towards modern phonology, by analyzing the structural or systemic independence of the dialectical areas in space and time. This vigorously controversial piece of scholarship confronts the ideas in vogue at the time in Romance dialectology, especially linguistic geography, held by Jules Gilliéron and his followers, in the light of methods used in general linguistics, which is still incipient in France and Western Europe. With other contributions from the same author in the RLaR, these two major papers from Georges Millardet are both an Opera aperta (as Umberto Eco coined it, i.e. an inexhaustible source of knowledge and insights) and a mirror of the pre- and post-WWI epoch, and of the current challenges met by the paradigms of Romance linguistics and dialectology, at any time.